Acute kidney injury and hyponatremia in hospitalized patients with rotavirus infection - Ulrike Hoffmann; Antje Rückner; Olaf Nickel; Kathrin Marx; Ralph Wendt (PLoS ONE, 2026)
Introduction Rotavirus is a common cause of infectious gastroenteritis in infants and children. The role of rotavirus infections in adults has potentially been underappreciated and there is a paucity of data on incidence and outcome of acute kidney injury in adult patients. Methods We conducted a retrospective cohort study of adult hospitalized patients with microbiologically confirmed rotavirus infection. The primary outcome was occurrence of acute kidney injury related to rotavirus infection. Secondary outcomes were in-hospital mortality, duration of hospitalization and occurrence of sodium disorders. Results 314 hospitalized adult patients with rotavirus infection (mean age 73.2 (± 15.6) years, 39.5% with diabetes mellitus and 33.4% with chronic kidney disease (CKD)) were evaluated. 200 patients (63.7%) had community-acquired and 114 patients (36.3%) had nosocomial rotavirus infection. Acute kidney injury (AKI) occurred in 127 (40.4%) patients. AKI occurred more often in patients with community-acquired than nosocomial infection (110 (55.0%) vs 17 (14.9%), p < 0.001). In the multivariate logistic regression analysis, preexisting CKD (OR 3.29, CI 1.92–5.77, p < 0.001) and community-acquired route of rotavirus infection (OR 8.00 (CI 4.43–15.3, p < 0.001) were significantly associated with the development of AKI. 26 (8.3%) patients died in hospital. Patients with AKI had worse survival (HR 2.63 (CI 1.20–5.74) p = 0.01). In the multivariate Cox regression analysis only age, but not AKI, was still significantly associated with mortality (HR 1.06, CI 1.01–1.11, p = 0.01). Hyponatremia was detected in 60 (30.6%) of 196 patients with community-acquired infection. Dehydration occurred in only 5 (2.6%) patients. Conclusion Adult outpatients with rotavirus infection and certain risk factors (e.g., CKD) have a high risk of developing AKI. Patients should seek medical attention with a low threshold and, if necessary, undergo hospitalization to counteract volume depletion and the development of acute renal injury. Hyponatremia frequently occurs while dehydration is rare. Recommendations in outpatients at risk for AKI should focus on increasing salt intake rather than water intake.